Inhibition of Human Acetylcholinesterase (4EY7) using Bioactive Compound from Moringa oleifera: Molecular Docking and Dynamic Studies - Utami, Wiji; Apriyanto, Apriyanto; Antari, Laila; Rasyid, Herlina; Fitriani, Ika Nur (Syarif Hidayatullah State Islamic University, 2024)
Alzheimer's disease is a neurodegenerative disorder caused by acetylcholine hydrolysis that impairs cognitive brain function. This research aims to determine the interaction and dynamic of ligands from Moringa oleifera on AChE through Lipinski's Rule, ADMET properties, molecular docking calculations, and molecular dynamic simulations. Lipinski's Rule calculation provided ligand limits that adhere to druglikeness properties. ADMET results also showed that several ligands satisfy ADMET properties. Pterygospermine has lower binding energy than the ligand control (-10.28 kcal mol-1) with amino acid residues of TYR133 and GLU202. It indicates a favorable interaction between the AChE receptor and ligand in the inhibition process. Based on molecular docking calculations, pterygospermine inhibits the AChE receptor at the Long, narrow aromatic gorge active site. According to molecular dynamic simulations, the MMPBSA energy for pterygospermine is 37.377 kJ mol-1. The samples showed a total average RMSD of 2 Å, suggesting no significant conformational changes throughout the simulation. The sample's average RMSF value is around 2 Å, suggesting favorable interactions with the receptor during simulation. However, this data is different from the ligand control interaction mode. Molecular dynamic investigations of the pterygospermine ligand in the complex revealed the stability and unfolded effect on the protein. The results of this study propose a candidate anti-Alzheimer's ligand from Moringa oleifera against the AChE receptor. In practice, these results can contribute to research studies exploring natural ingredients from plants with medicinal potential in drug discovery. These results can be validated using further research in vitro and in vivo.